PERBANDINGAN EFEKTIVITAS STRATEGI TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP TINGKAT PROFITABILITAS PERUSAHAAN DALAM SRI-KEHATI INDEX (STUDI PADA METODE CAUSE BRANDING, VENTURE PHILANTROPHY DAN MIX METHOD) - ERIANA, DEWI (Jurnal Akuntansi AKUNESA, 2013)
The introduction of Law No. 40 of 2007 and SRI-KEHATI index are the fact that CSR play animportant role in the corporate developments. Based on these phenomena, the purpose of thisresearch was to compare and find out differences of effectiveness csr strategy whichmeasured by three methods of csr (cause branding, venture philantrophy, mix method).Return On Asset (ROA) used as financial performance indicators. This research usedstratified sampling method with 18 samples and one-way ANOVA for hypotheses test. Theresults of this research conclude that there was significant differences on Mix Method totheir profitability.Keywords: Corporate Social Responsibility (CSR), Cause Branding, Venture Philantrophy,SRI-KEHATI index, Return On Asset (ROA)